2017
DOI: 10.1007/s40617-017-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing PEAK Relational Training System to Teach Visual, Gustatory, and Auditory Relations to Adults with Developmental Disabilities

Abstract: Two multiple baseline designs were conducted across participants to determine if the promoting the emergence of advanced knowledge (PEAK) equivalence module was an effective tool in teaching adults with autism relationships between stimuli. More specifically, a transitivity program utilizing the gustatory sensory modality was implemented. Stimuli were selected and probed initially preceding the training. First, gustatory stimuli to a visual picture were trained. Then, a visual picture to a spoken word was trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The evaluation of long-term maintenance of training is another strength of the present study. Some relational training studies tested emergent responses upon completion of training and did not evaluate whether these responses maintained (e.g., McKeel & Matas, 2017;Mullen et al, 2017;Toussaint & Tiger, 2010). All three children in the present study maintained APP at a relatively high level at 7-and 10-week follow-ups, indicating that the intervention had a sustainable effect.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The evaluation of long-term maintenance of training is another strength of the present study. Some relational training studies tested emergent responses upon completion of training and did not evaluate whether these responses maintained (e.g., McKeel & Matas, 2017;Mullen et al, 2017;Toussaint & Tiger, 2010). All three children in the present study maintained APP at a relatively high level at 7-and 10-week follow-ups, indicating that the intervention had a sustainable effect.…”
Section: Discussionmentioning
confidence: 68%
“…Previous research has demonstrated that multiple sensory modalities are important learning channels for facilitating the emergence of untaught relations (Annett & Leslie, 1995;Bush, 1993;McKeel & Matas, 2017;Mullen et al, 2017;Toussaint & Tiger, 2010). Horne and Lowe (1996) provide an example.…”
mentioning
confidence: 99%
“…Entre os artigos que utilizaram o livro equivalência, a maior parte teve como objetivo o desenvolvimento de comportamentos específicos como habilidades acadêmicas Dixon, Belisle, Stanley, Daar, & Williams, 2016; ou relação entre diferentes sistemas sensoriais (Mullen et al, 2017;McKeel & Matas, 2017b;Dixon, Belisle, Stanley, et al, 2017).…”
Section: Livro Equivalênciaunclassified
“…Some studies report that gustatory referents effectively contribute to associative learning among multisensory features for people with autism or developmental disabilities (e.g., [ 19 , 20 , 21 , 22 ]), since the learning of linguistic and gustatory stimuli helps with their word learning. People with autism have language delay or impairment [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a behavioral study, after three autistic children studied associative pairs of gustatory and visual features and associative pairs of visual and auditory features, two children could also study derived transitive pairs of gustatory and auditory features [ 21 ]. Another study reports that the Promoting the Emergence of Advanced Knowledge equivalent module, which is a development curriculum, may be effective while teaching adults with autism the relationships between multisensory features (gustatory, visual, and auditory stimuli) to improve their derived relational skills [ 22 ]. These findings about people with developmental disabilities are also consistent with a previous finding about healthy subjects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%